Studies on floral sources, phenolic, flavonoid, proline contents and antioxidant capacity of honey from the Khirsoo area of Pauri, Uttarakhand, India - UNIYAL, P L; TIWARI, P; CHAUDHARY, EKTA (The Indian Journal of Agricultural Sciences, 2018)
Present study was carried out to determine the floral sources, phenolic, flavonoid, proline contents and antioxidant capacity of 24 honey samples collected from the Khirsoo area of the Pauri district, Uttarakhand (India). The phenolic, flavonoid, proline contents, and antioxidant capacity of the honey samples ranged from 36.83 to 106.66 mg GAE/100g, 3.99 to 20.56 mg QE/100g, 27.3 to 621.22 mg/kg and 16.24 to 25.96 mg AAE/100g, respectively. Maximum quantity of phenolic, flavonoid contents and antioxidant capacity was found in Thapla honey representing the dominant floral sources Aesculus indica, Rhododendron arboreum, Myrica esculentum, Berberis aristata, Coriandrum sativa, Brassicaceous and Rosaceous members. Highest proline content was found in Gwaad honey, extracted in the month of November with dominant bee forage species Prunus cerasoides, Sesamum indicum, Impatiens balsaminea, Zeamays and Luffa spp. Study has shown that there is a positive correlation between the antioxidant capacity and phenolic contents (R=0.844) as well as in between antioxidants and the flavonoid contents (R=0.694). The observation revealed that the region has a good potential of bee forage species and quality of honey is good for dietary and medicinal purpose.